Photonics-based mid-infrared interferometry: 4-year results of the ALSI project and future prospects - Labadie, Lucas; Minardi, Stefano; Tepper, Jan; Diener, Romina; Muthusubramanian, Balaji; Pott, Jorg-Uewe; Nolte, Stefan; Gross, Simon; Arriola, Alexander; Withford, Michael J. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
In this contribution, we review the results of the ALSI project (Advanced Laser-writing for Stellar Interferometry), aimed at assessing the potential of ultrafast laser writing to fabricate mid-infared integrated optics (IO) devices with performance compatible with an implementation in real interferometric instruments like Hi5 or PFI. Waveguides for the L, L' and M bands with moderate propagation losses were manufactured in Gallium Lanthanum Sulfide and ZBLAN glasses and used to develop photonic building blocks as well as a full mid-IR 4-telescope beam combiner. We discuss the advantages and disadvantages of the tested combiners and discuss a possible roadmap for the continuation of this work.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Astrophotonics; Integrated Optics; long-baseline interferometry; optical/infrared instrumentation